PEMANFAATAN PUPUK HAYATI CACING TANAH UNTUK MENINGKATKAN EFISIENSI PENGELOLAAN TANAH PERTANIAN LAHAN KERING - Subowo Subowo (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Agriculture development that is oriented to the efficient use of the natural resources and environmental save sound has boosted the effort to obtain the best concept in land management for agricultural product. The dynamic of land approaches and land ecosystem are important. In general upland area in wet tropical region has a compacted subsurface horizon and low organic material, hence the population of the detritivor low and plant soil born diseases organisms exist and develop.The burrower soil fauna such as earthworm will prevent soil compaction, increase soil aeration, and mixing of soil and organic matter in the surface and subsurface. Therefore, the potential use of earthworm as biologic agent to increase soil fertility and sustain land productivity to obtain the efficient use of organic wastes, farming systems, soil management, fertilization and the protection of plant soil born diseases.